Rethinking the Burden of Traditional Informed Consent Prior to Prenatal Genetic Screening - Allyse, Megan (The Hastings Center report, 2025)
The ethics literature and professional guidelines call for extensive discussions prior to prescreening consent to prenatal cell-free DNA screening to, theoretically, allow patients to make decisions that match their values and goals of care. Most patients, however, actively avoid in-depth moral deliberation when consenting to prenatal screening and then receive a screen-negative result, suggesting that an information-heavy process is irrelevant for average-risk pregnancies. In addition, extensive information-based consent procedures are not feasible in many resource-limited contexts. Meanwhile, patients and families with screen-positive results frequently report minimal support following screening, resulting in long-term distress and suboptimal outcomes. We argue for a fundamental shift to an approach we call “just-in-time consent”: identifying the essential information for values-based decisions prior to screening while relocating resources and moral deliberation to when families receive screen-positive results. This model both ensures that patients and families receive support when they most need it and maintains high standards for the ethical provision of prenatal genetic screening.